Digital asset arbitrage - Pritchard, Brendan Padraic Anson (2018)
The study examines the risk and reward potential of arbitrage in the digital asset market. Specifically, it looks at exchange to exchange and statistical arbitrage, or pairs trading, for the cryptocurrencies, Bitcoin (BTC) and Litecoin (LTC). In this instance they are traded on the LTC/BTC pair. The LTC/BTC is examined with pairs trading by performing statistical tests and implementing automated trading strategy to determine potential profit levels. Subsequently, additional trading strategies are examined based on the concepts of the statistical results in this study and other technical analysis indicators. The study outlines the profit potential of exchange to exchange arbitrage but also shows how this type of arbitrage is in fact quite risky and not as simple as the large spreads would suggest. Pairs trading strategies are instead put forward as a method of profiting on the price movement disparities in the digital asset market without running the same risks as exchange to exchange arbitrage. The strategies proposed are based on statistical tests as well as technical analysis indicators that both aim at predicting price trend and direction and try to profit off abnormal price movements and subsequent normalization. It turns out that a range of profit levels can be achieved. All though the strategies proposed are too rudimentary to consider for live trading, they do prove the basic proof of concept that there are ways to profit from pairs trading in the digital asset market. Trading strategies can be formed that provide considerable returns while reducing risk that would otherwise be encountered with long term investment positions and/or exchange to exchange arbitrage in the digital asset market.